The Role of BIM in Supporting Circularity: A Conceptual Framework for Developing BIM-Based Circularity Assessment Models in Buildings - Rand Askar; Ferhat Karaca; L. Bragança; Helena Gervásio (Springer Nature Switzerland, 2024)
The simultaneous evolution of the construction sector towards the circular economy and digitalization is widely recognized and endorsed by both policy initiatives and academic discourse. In this dynamic landscape, research efforts are focused on creating automated tools and models to facilitate the implementation and monitoring of circularity in buildings, thereby enhancing efficiency and effectiveness of decision-making processes. Building Information Modelling (BIM) stands out for its acknowledged capabilities in data storage and process automation, making it a compelling platform for achieving these objectives. This paper aims to establish a conceptual framework that addresses the challenge of developing BIM-supported tools and models for promoting circularity in buildings. The primary goal of the proposed framework is to assist tool developers and professionals in the construction sector, providing them with a systematic approach to integrate circularity aspects into BIM for efficient and automated assessment processes. To achieve this, the study critically analyzes five existing BIM-based circularity tools and models from previous studies, elucidating the key stages and providing detailed steps for their development. The paper concludes by emphasizing the main barriers hindering the development and automation of circularity tools within the BIM framework. This comprehensive exploration contributes to the ongoing discourse on sustainable construction practices, offering valuable insights for practitioners, researchers, and policymakers striving to advance the integration of circular and digital principles in the construction industry.
Keywords: Building information modeling; Computer science; Architectural engineering; Systems engineering; Engineering; Construction engineering; Operations management; Scheduling (production processes); type of access: open access